Preparation of Pb(Zr, Ti)O3 thin films sputtered from a multi-element metallic target - Nguyen, Huy Thanh; Vu, Hung Ngoc; Nguyen, Thuy Phu (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts